2008
DOI: 10.3151/jact.6.365
|View full text |Cite
|
Sign up to set email alerts
|

Shear Fatigue Response of Cracked Concrete Interface

Abstract: The shear fatigue behavior of cracked concrete interface was experimentally investigated on a single crack plane to quantify the degree of deterioration per load cycle. A simple experimental setup was used, in which a finite lateral stiffness was provided to the crack interface by using unbonded steel bars. The effects of loading amplitude, loading pattern and water exposure were examined. Time-dependent behavior of shear transfer under sustained shear load was also investigated. The shear fatigue response of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…Through a parametric study, it was shown that the reduction in the fatigue life of bridge decks is attributed to shear fatigue phenomenon on crack interfaces. The reduction is particularly significant when water is present in the cracks [1,12], which is consistent with the observations by [13]. Gebreyouhannes performed shear fatigue simulations on reinforced concrete beams with and without web reinforcement under both pulsating and moving loads [14].…”
Section: Introductionsupporting
confidence: 86%
“…Through a parametric study, it was shown that the reduction in the fatigue life of bridge decks is attributed to shear fatigue phenomenon on crack interfaces. The reduction is particularly significant when water is present in the cracks [1,12], which is consistent with the observations by [13]. Gebreyouhannes performed shear fatigue simulations on reinforced concrete beams with and without web reinforcement under both pulsating and moving loads [14].…”
Section: Introductionsupporting
confidence: 86%
“…However, when liquid water is present and water advection occurs, fine fragments are transported away from their original location to other locations as the result of liquid water advection, and new intact surfaces are constantly exposed to the mechanical action from the base plate. The decrease of shear transfer through washout has already been pointed out in another study (Gebreyouhannes et al 2008), and a similar mechanism is considered to be at work in the present experiment, promoting breakdown.…”
Section: Discussion Of Acceleration Mechanism Of Concrete Damage By Lmentioning
confidence: 54%
“…The causal mechanisms have been variously identified as reduction in compressive strength due to changes in surface energy (Gilkey 1926;Matsushita 1984;Matsushita and Onoue 2006), the cracked surface washout effect (Gebreyouhannes et al 2008), the wedge effect (Slowik and Saouma 2000), and cavitation (Maekawa and Fujiyama 2013), among other things, yet the influence of water on this anchorage performance has not been fully elucidated. A case similar to the damage discussed here was reported by Matsuda in a study on the concrete around bridge supports degrading into a mud pumping state and the estimation of the mechanism (Matsuda 2013), but that study have gone no futher the shortening the quantitative analysis required for the actual design and operation taking into account the influence of the above on structural performance deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…If we consider the more detailed behavior of the contact surface, such as frictional stress, change of inclination, and permanent damage of contact unit, in modeling the constitutive relation of local contact stress, a more sophisticated shear transfer model can be obtained (Gebreyouhannes et al 2008). However, such rigorous numerical work is too expensive to be directly implemented at the inner loop of nonlinear analysis.…”
Section: Shear Transfer Model For Cracked Concretementioning
confidence: 99%